The Correlation Between Pronunciation and Student’s Reading Aloud : English - Sirrul Bari; Selfi Usmani Putri (JOEY: Journal of English Ibrahimy, 2025)
The study aimed to find out the correlation between students’ reading aloud and pronunciation at the eleventh TJKT 2 grade of SMK Negeri Kalibaru. The researcher applied a correlation method. The study was carried out into one class. The population of this research is 480 from all of eleventh class. The sample of this study consisted of 35 students of the eleventh TJKT 2 grade of SMK Negeri Kalibaru, the sample used was cluster sampling. The data was collected by questionnare and oral test. The result of data used Pearson product moment SPSS 21. The finding of the reserch indicates that there were the significant and correlation between student’s reading aloud and pronunciation. According to the level of Pearson correlation, r count 0,738 > r table 0,325. There was high correlation between both of variables. There score sig was 0,000 < 0,005. Alternative hypothesis is accepted. It means reading aloud and pronunciation were positive significant, in English lesson as foreign languange at the eleventh grade of SMK Negeri Kalibaru BanyuwangiThe study aimed to find out the correlation between students’ reading aloud and pronunciation at the eleventh TJKT 2 grade of SMK Negeri Kalibaru. The researcher applied a correlation method. The study was carried out into one class. The population of this research is 480 from all of eleventh class. The sample of this study consisted of 35 students of the eleventh TJKT 2 grade of SMK Negeri Kalibaru, the sample used was cluster sampling. The data was collected by questionnare and oral test. The result of data used Pearson product moment SPSS 21. The finding of the reserch indicates that there were the significant and correlation between student’s reading aloud and pronunciation. According to the level of Pearson correlation, r count 0,738 > r table 0,325. There was high correlation between both of variables. There score sig was 0,000 < 0,005. Alternative hypothesis is accepted. It means reading aloud and pronunciation were positive significant, in English lesson as foreign languange at the eleventh grade of SMK Negeri Kalibaru Banyuwangi